PENGARUH PENGGUNAA KARTU UNSUR PADA MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT TERHADAP HASIL BELAJAR SISWA MATERI KONSEP STRUKTUR ATOM DI KELAS X SMA 3 BIROMARU - Jainuri, Ahmat (JSTT, 2015)
The research aim is to know the influence of using element cards on cooperative learning model of team game tournament (TGT) type forwardsstudent learning outcomes about material of atomic structure concept at year X SMA Negeri 3 Biromaru. The research method used quasy experiment. The population of the research was all class X Student of SMA Negeri 3 Biromaru which had been selected purposively. The sample was year X of Sains students (I) as a goup exsperiment. and whereas year X of Sains students (II) as a control group. The independent variable was the model of cooperative learning of TGT type by using element cards whereas the dependent variable was the student learning outcomes. The result data consisted of student learning outcomes (posttest), questioners of student activity, responses of student acivity, and documentation. The average cognitive of student learning outcomes (86,26) for the exsperimental group was higher then the control group (74,50 ). The average of student activity result (57,89) with percentage 86,20 % was categorized as good, and the average response student activity forwarded the use of elements cards on cooperative learning model of TGT type was 84,42 %. The percentage was categorized as high (60 %) and it considered as a positive criterion which was belong to the exsperimental group. It can be concluded that the using of element cards on cooperative learning model of TGT type has a positive influence forwards student learning outcomes about atomic structure concepts.